Eicosapentaenoic acid to arachidonic acid (EPA/AA) ratio as an associated factor of high risk plaque on coronary computed tomography in patients without coronary artery disease. (July 2016) - Nagahara, Yasuomi; Motoyama, Sadako; Sarai, Masayoshi; Ito, Hajime; Kawai, Hideki; Takakuwa, Yoko; Miyagi, Meiko; Shibata, Daisuke; Takahashi, Hiroshi; Naruse, Hiroyuki; Ishii, Junichi; Ozaki, Yukio
Abstract: Background and aims: Coronary computed tomography angiography (CCTA)-verified high risk plaque (HRP) characteristics including positive remodeling and low attenuation plaque have been associated with acute coronary syndromes. Several studies reported that the n-3 polyunsaturated fatty acids have been associated with cardiovascular events. However, the relationship between serum eicosapentaenoic acid to arachidonic acid (EPA/AA) ratio and CCTA-verified HRP in patients without known coronary artery disease (CAD) is unclear. We aimed at investigating the relation between EPA/AA and CCTA-verified HRP in patients without known CAD. Methods: We included 193 patients undergoing CCTA without known CAD (65.5 ± 12.0 years, 55.0% male). No patient has been treated with EPA. The relation of coronary risk factors, lipid profile, high-sensitivity C-reactive protein, coronary artery calcification score (CACS), number of vessel disease, plaque burden, and EPA/AA with the presence of HRP was evaluated by logistic regression analysis. Incremental value of EPA/AA to predict HRP was also analyzed by C-index, NRI, and IDI. A Cox proportional hazards model was used to estimate the time to cardiovascular event. Results: HRP was observed in 37 (19%) patients. Multivariable logistic regression analysis revealed that current smoking (OR 2.58; p = 0.046), number of vessel disease (OR 1.87; p = 0.031), and EPA/AA ratio (OR 0.65; p = 0.0006) were independent associated factors of HRP on CCTA. Although the addition of EPA/AA to the baseline model did not significantly improve C-index, both NRI (0.60, p = 0.0049) and IDI (0.054, p = 0.0072) were significantly improved. Patients with HRP had significantly higher rate of events compared with patients without HRP (14% vs. 3%, Logrank p = 0.0004). On multivariable Cox hazard analysis, baseline EPA/AA ratio was an independent predictor (HR 0.57, p = 0.047). Conclusions: Low EPA/AA was an associated factor of HRP on CCTA in patients without CAD. In addition to conventional coronary risk factors and CACS, EPA/AA and CCTA might be useful for risk stratification of CAD. Highlights: This paper focused on the primary prevention of coronary artery disease (CAD). High risk plaques (HRP) on CCTA was related with low EPA/AA in patients without previous CAD. EPA/AA had incremental value over CT parameters such as coronary calcium score, number of vessel disease, and plaque burden as well as conventional risk factors to predict HRP on CCTA. Male, number of vessel disease, and HRP were independent predictors of cardiovascular events.